Dialect, Culture, and Society in Eastern Arabia, Volume 1 Glossary - Holes, Clive (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
Dialect, Culture, and Society in Eastern Arabia is a three-volume study of the Arabic dialects spoken in Bahrain by its older generation in the mid-1970s, and the socio-cultural factors that produced them. Volume 1: Glossary , published in 2001, lists all the dialectal vocabulary, with extensive contextual exemplification, and cross-referenced to other lexica, which occurred in the complete set of texts recorded during fieldwork. Volume 2: Ethnographic Texts presents a selection of these texts, transcribed, annotated and translated, and with detailed background essays, covering major aspects of the pre-oil culture of the Gulf and the initial stages of the transition to the modern era: pearl diving, agriculture, communal relations, marriage, childhood, domestic life, work. Excerpts from local dialect poems concerned with these subjects are also included. Volume 3: Phonology, Morphology, Syntax, Style is based on an extensive archive of recorded material, gathered for its ethnographic as well as its purely linguistic interest.